Analisis Penerapan Target Costing Sebagai Sistem Pengendalian Biaya Produksi Untuk Meningatkan Laba Pada PT. Maleo Rachma Indo Abadi - Nur Amaliah Hasanah; Indra Cahya Kusumla; Didi Didi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research aims to find out how to calculate the cost of production using the full costing method to determine the selling price of products. In determining the selling price, the cost-plus pricing method is used, namely determining the selling price by adding a certain profit margin to the total production costs. The research method used is quantitative descriptive analysis. The research results show that calculating the cost of goods manufactured using the full costing method provides benefits, and the cost of goods sold and cost of production must be calculated at the beginning of each month based on the previous period's sales report. The main problem in this research is determining the selling price of a product. This determination is based on the calculation of the cost of production, which includes determining the cost elements that form the basis of the cost of the product. The selling price set must be able to cover all costs and generate long-term profits. Determining the correct product cost price can reduce uncertainty in setting selling prices.